A counterexample to a uniqueness result - Ramm, Alexander G. (My University, 2010)
A counterexample is given to the uniqueness result given in the paper by J.Cox and K.Thompson, ”Note on the uniqueness of the solution of an equation of interest in inverse scattering problem”, J. Math.Phys., 11, N3, (1970), 815-817.
Keywords: Uniqueness; Inverse scattering